Structural Connectivity is Differently Altered in Dementia with Lewy Body and Alzheimer’s Disease - Delli Pizzi, Stefano; Franciotti, Raffaella; Taylor, John-Paul; Esposito, Roberto; Tartaro, Armando; Thomas, Astrid; Onofrj, Marco; Bonanni, Laura (Frontiers in Aging Neuroscience, 2015)
The structural connectivity within cortical areas and between cortical and subcortical structures was investigated in dementia with Lewy bodies (DLB) and Alzheimer’s Disease (AD). We hypothesized that white matter (WM) tracts which are linked to visual, attentional and mnemonic functions would be differentially and selectively affected in DLB as compared to AD and age-matched control subjects. Structural and diffusion tensor imaging (DTI) were performed on 14 DLB patients, 14 AD patients and 15 controls. DTI-metrics related to WM damage were assessed within tracts reconstructed by FreeSurfer's TRACULA pipeline. Correlation analysis between WM and grey matter (GM) metrics was performed to assess whether the structural connectivity alteration in AD and DLB could be secondary to GM neuronal loss or a consequence of direct WM injury. Anterior thalamic radiation and cingulum-cingulate gyrus were altered in DLB, whereas cingulum-angular bundle was disrupted in AD. In DLB patients, secondary axonal degeneration within anterior thalamic radiation was found in relation to microstructural damage within medio-dorsal thalamus, whereas axonal degeneration within cingulum-angular bundle was related to precuneus thinning. WM alteration within the uncinate fasciculus was present in both groups of patients and was related to frontal and to temporal thinning in DLB and AD, respectively. We found structural connectivity alterations within fronto-thalamic and fronto-parietal (precuneus) network in DLB whereas, in contrast, disruption of structural connectivity of mnemonic pathways was present in AD. Furthermore, the high correlation between GM and WM metrics suggests that the structural connectivity alteration in DLB could be linked to GM neuronal loss rather than by direct WM injury. Thus, this finding supports the key role of cortical and subcortical atrophy in DLB.